Distribution and Occurrence Frequency of dB/dt Spikes During Magnetic Storms 1980–2020 - A. Schillings; L. Palin; H. J. Opgenoorth; M. Hamrin; L. Rosenqvist; J. W. Gjerloev; L. Juusola; R. Barnes (Space Weather)
Abstract The physical magnetospheric cause for geomagnetically induced currents (GICs) are rapid time‐varying magnetic fields (dB/dt), which occur mainly during magnetic substorms and storms. When, where and why exactly such rapid dB/dt may occur is insufficiently understood. We investigated all storms since 1980 and analyzed the negative and positive dB/dt spikes (>|500| nT/min) in the north and east component using a worldwide coverage (SuperMAG). Our analysis confirmed the existence of two dB/dt spikes “hotspots” located in the pre‐midnight and in the morning magnetic local time sector, independently of the geographic location of the stations. The associated physical phenomena are probably substorm current wedge onsets and westward traveling surges (WTS) in the evening sector, and wave‐ or vortex‐like current flows in the morning sector known as Omega bands. We observed a spatiotemporal evolution of the negative northern dB/dt spikes. The spikes initially occur in the pre‐midnight sector, and then develop in time toward the morning sector. This spatiotemporal sequence is correlated with bursts in the AE index, and can be repeated several times throughout a storm. Finally, we investigated the peak value of Dst and AE during the storm period in comparison with the dB/dt spike occurrence frequency, we did not find any correlation. This result implies that a moderate storm with many spikes can be as (or more) dangerous for ground‐based infrastructures than a major storm with fewer dB/dt spikes. Our findings regarding the physical causes and characteristics of dB/dt spikes may help to improve the GIC forecast for the affected regions.